Língua brasileira de sinais: percepções de um docente - Almeida, Genisvaldo Rafael Mourão de (Universidade Federal do Tocantins, 2023)
ABSTRACT: The present work was carried out through a bibliographic review, with a qualitative approach, having as main objective to highlight the historical events that contributed to the appearance of the Brazilian Sign Language, as well as to base the importance of Libras in the social development of the deaf from the perception and perspective of the teacher who works in a regular school as he interprets to emphasize the importance of the educational inclusion of the deaf that has been frequently debated, especially due to the bilingual and bicultural condition of the students, which requires different teaching practices that start from the Brazilian Sign Language. Libras since its emergence has enabled deaf people to have better interpersonal interaction, providing them with integration in various areas of society, demystifying the idea that deaf people would have intellectual disabilities, not being able to develop any type of activities, whether educational or not. The work as a teacher of Libras and also while interpreting in regular schools, enables the experience and real context of the deaf experience in the context of a society in which the majority is not and is not prepared for real coexistence with the deaf subject, hindering the experience of the school as the place where the exchange of knowledge and intercultural relations occurs, the truth is that in it the deaf student inserted in the context of the school routine manages to be recognized as an individual, participant in the society in which he is inserted and then, no less important the perception on the part of the school community of culture, language and the very existence of the deaf in society, awakening in many the desire to get to know better and to interact with this enchanting universe, libras and its cultural interaction.